Anonymity handover authentication protocol based on group signature for wireless Mesh network - Bin-ting SU; Li XU; Feng WANG; NZhi-xing LI (Tongxin xuebao)
In order to ensure that the Mesh network mobile client video,voice and other real-time strong applications without interruption,a secure and efficient handover authentication was very important.To protect the privacy of mobile nodes,an anonymity handover authentication protocol was proposed based on group signature for wireless mesh network.Compared with other handover authentication protocols based on group signature,the proposed scheme did not involve the group signature correlation operation,and the group signature algorithm was only carried out on the router.The pro-posed protocol not only enhances the security but also performs well in authentication efficiency and privacy-preserving.